Hadith #103 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Whenever `Aisha (the wife of the Prophet) heard anything which she did not understand, she used to ask again till she understood it completely. Aisha said: “Once the Prophet (ﷺ) said, “Whoever will be called to account (about his deeds on the Day of Resurrection) will surely be punished.” I said, “Doesn’t Allah say: “He surely will receive an easy reckoning.” (84.8) The Prophet (ﷺ) replied, “This means only the presentation of the accounts but whoever will be argued about his
Grade: Sahih

Hadith #580 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
I was with Buraida on a cloudy day and he said, “Offer the `Asr prayer earlier as the Prophet (ﷺ) said, ‘Whoever leaves the `Asr prayer will have all his (good) deeds annulled.” (See Hadith No. 527 and 528)
Grade: Sahih

Hadith #1071 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Only Um Hani told us that she had seen the Prophet (p.b.u.h) offering the Duha (forenoon prayer). She said, “On the day of the conquest of Mecca, the Prophet (ﷺ) took a bath in my house and offered eight rak`at. I never saw him praying such a light prayer but he performed perfect prostration and bowing.
Grade: Sahih

Hadith #2415 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
I wrote a letter to Ibn `Abbas and he wrote to me that the Prophet (ﷺ) had given the verdict that the defendant had to take an oath.
Grade: Sahih

Hadith #2562 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Ibn `Abbas wrote that the Prophet (ﷺ) gave his verdict on the basis of the defendant’s oath.
Grade: Sahih

Hadith #2972 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
`Aisha said, “The Prophet (ﷺ) died in my house on the day of my turn while he was leaning on my chest closer to my neck, and Allah made my saliva mix with his Saliva.” `Aisha added, “`AbdurRahman came with a Siwak and the Prophet (ﷺ) was too weak to use it so I took it, chewed it and then (gave it to him and he) cleaned his teeth with it.”
Grade: Sahih

Hadith #3601 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Muawiya offered one rak`a witr prayer after the `Isha prayer, and at that time a freed slave of Ibn `Abbas was present. He (i.e. the slave) went to Ibn `Abbas (and told him that Muawiya offered one rak`a witr prayer). Ibn `Abbas said, “Leave him, for he was in the company of Allah’s Messenger (ﷺ).”
Grade: Sahih

Hadith #4269 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Abu Al-Khair said, “As-Sanabih, I asked (me), ‘When did you migrate?’ I (i.e. Abu Al-Khair) said, ‘We went out from Yemen as emigrants and arrived at Al-Juhfa, and there came a rider whom I asked about the news. The rider said: We buried the Prophet (ﷺ) five days ago.” I asked (As-Sanabihi), ‘Did you hear anything about the night of Qadr?’ He replied, ‘Bilal, the Mu’adh-dhin of the Prophet (ﷺ) informed me that it is on one of the seven nights of the last ten days (of Ramada
Grade: Sahih

Hadith #4321 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Ibn `Abbas recited: “(Respite will be granted) until when the Apostles gave up hope (of their people) and thought that they were denied (by their people). There came to them Our Help ….” (12.110) reading Kudhibu without doubling the sound ‘dh’, and that was what he understood of the Verse. Then he went on reciting: “..even the Apostle and those who believed along with him said: When (will come) Allah’s Help? Yes, verily, Allah’s Help is near.” (2.214) Then I met `Urwa bin Az-Zu
Grade: Sahih

Hadith #4346 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Two women were stitching shoes in a house or a room. Then one of them came out with an awl driven into her hand, and she sued the other for it. The case was brought before Ibn `Abbas, Ibn `Abbas said, “Allah’s Messenger (ﷺ) said, ‘If people were to be given what they claim (without proving their claim) the life and property of the nation would be lost.’ Will you remind her (i.e. the defendant), of Allah and recite before her:–“Verily! Those who purchase a small gain at the cost of
Grade: Sahih

Hadith #4547 - Sahih al-Bukhari - Ibn Abu Mulaikah (Sahih al-Bukhari)
Ibn `Abbas asked permission to visit Aisha before her death, and at that time she was in a state of agony. She then said. “I am afraid that he will praise me too much.” And then it was said to her, “He is the cousin of Allah’s Messenger (ﷺ) and one of the prominent Muslims.” Then she said, “Allow him to enter.” (When he entered) he said, “How are you?” She replied, “I am Alright if I fear (Allah).” Ibn `Abbas said, “Allah willing, you are Alright as you are the wife of
Grade: Sahih